Strategy for Increasing Halal Products and Halal Certification of Food Products in Increasing the Competitiveness of the Indonesian Halal Industry - Melga Sari, Diny; Noviarita, Heni; Iqbal Fasa, Muhammad (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
As the Muslim population continues to grow globally, demand for halal products is also increasing. Initially, halal products may have had limited availability. However, halal products have now become a trend that is not only a consumer need, but also an obligation for manufacturers to produce. The purpose of this study is to determine the Strategy for Increasing Halal Products and Halal Certification of Food Products in Improving the Competitiveness of the Indonesian Halal Industry. The method in this study uses a qualitative approach. This study relies on secondary data, which includes literature studies written by economic experts, as well as literature from various print institutions and other related electronic media. This study uses descriptive methods, which are conducted by examining various related information. The results of this study indicate that there are five strategies in encouraging increased halal products, namely competitiveness for mapping, certification for market access, promotion and marketing, coordination and policy synergy, international cooperation. Meanwhile, the strategy in encouraging increased certification of halal food products is that halal labels are considered important and become one of the halal product development strategies because consumers tend to be aware and believe that products with halal labels are guaranteed and in accordance with sharia rules.